Optimizing diabetes control in people with Type 2 diabetes through nurse‐led telecoaching. Issue 6 (9th March 2016) - Odnoletkova, I.; Goderis, G.; Nobels, F.; Fieuws, S.; Aertgeerts, B.; Annemans, L.; Ramaekers, D.
Abstract : Aims: To study the effect of a target‐driven telecoaching intervention on HbA1c and other modifiable risk factors in people with Type 2 diabetes. Methods: We conducted a randomized controlled trial in patients receiving hypoglycaemic agents. The primary outcome was HbA1c level at 6 months in the entire sample and in a subgroup with HbA1c levels ≥ 53 mmol/mol (7%) at baseline. Secondary outcomes were HbA1c at 18 months; total cholesterol, LDL, HDL, triglycerides, blood pressure, BMI and proportion of people who had achieved guideline‐recommended targets at 6 and 18 months. Results: A total of 287 participants were randomized to telecoaching and 287 to usual care. The mean (sd ) baseline HbA1c level was 53 (11) mmol/mol [7.0 (1.0)%] overall and 63 (10) mmol/mol [7.9 (0.9)%] in the elevated HbA1c subgroup. At 6 months, the between‐group differences in favour of telecoaching were: HbA1c ‐2 (95% CI ‐4; ‐1) mmol/mol [‐0.2 (95% CI ‐0.3;‐0.1)%; P =0.003] overall and ‐4 (95% CI ‐7; ‐2) mmol/mol [‐0.4 (95% CI ‐0.7; ‐0.2)%; P =0.001] in the elevated HbA1c subgroup; BMI ‐0.4 kg/m 2 (95% CI ‐0.6; ‐0.1; P =0.003); total cholesterol ‐6 mg/dl (95% CI ‐11; ‐1, P =0.012). The proportion of participants on target for the composite of HbA1c, LDL and blood pressure increased by 8.9% in the intervention group and decreased by 1.3% in the control group ( P =0.011). At 18 months, the difference in HbA1c was: ‐2 (95% CI ‐3;‐0) mmol/mol [‐0.2 (95% CI ‐0.3; ‐0.0)%; P =0.046] overall and ‐4 (‐7; ‐1) mmol/mol [‐0.4 (95% CI ‐0.7; ‐0.1)%; P =0.023] in the elevated HbA1c subgroup. Conclusion: Nurse‐led telecoaching improved glycaemic control, total cholesterol levels and BMI in people with Type 2 diabetes. Twelve months after the intervention completion, there were sustained improvements in glycaemic control. What's new?: Tele‐education programmes may improve access to diabetes care, but their effectiveness is uncertain. This clinical trial was the first to test an Australian target‐driven telecoaching intervention, the COACH programme, for patients with Type 2 diabetes in Europe. The intervention group showed an improvement in glycaemic control that was sustained for at least 12 months after the completion of the intervention. Such a sustainability of effect had not previously been demonstrated by other diabetes self‐management support programmes. The distinguishing features of the COACH programme, patient empowerment, goal setting, advice on lifestyle and medication adjustments, and engaging physicians, could guide designers of diabetes education programmes and inspire diabetes educators.